Isolated bacteria from ice cubes sampled from food premises in Kuala Pilah, Negeri Sembilan / Wan Shahirah W Adnan - W Adnan, Wan Shahirah (2017)
The aims of this study are to isolate bacteria and determine pathogenic bacteria present in edible ice served in drinks and beverages. The consumption of ice cube in drinks and beverages as coolant agent is very common in Kuala Pilah, Negeri Sembilan. Thus, contamination in ice cube may be a vehicle in transmission of disease to the public. The ice cube samples were collected randomly from food premises in Pekan Kuala Pilah, Negeri Sembilan. The samples collected filtered using cellulose nitrate membrane (0.45 μm pore size, 47 mm diameter) and proceed with placement of membrane on MacConkey and nutrient agar. Successfully isolated bacteria were tested using IMViC test and gram staining to determine their characteristics. The species and genus of the isolated bacteria were then confirmed with DNA sequencing. Succesfully isolated bacteria were identified as Klebsiella pneumoniae, Acinetobacter baumanii, and Bacillus lichenifromis. Klebsiella pneumoniae were isolated from two out of three samples collected.